GUGATAN CLASS ACTION SEBAGAI PENEGAKAN HUKUM PRIVAT ATAS PRODUK PALSU YANG MEMBAHAYAKAN KESELAMATAN KONSUMEN - Saputra, Rio; Darmawan, Didit (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This literature study aims to reconstruct the class action lawsuit as an effective private enforcement instrument in addressing counterfeit products that endanger consumer safety. Employing a qualitative normative juridical method with content analysis techniques, this research examines secondary data from legislation, legal literature, and judicial practices. The findings indicate that the theoretical construction of class action requires a paradigm shift from mere procedural efficiency to an active private enforcement mechanism prioritizing consumer safety. Normative and procedural critical points, particularly in proving collective causation and calculating latent damages, can be overcome through risk-based evidence, a redefinition of commonality, and a differentiated compensation scheme. An effective enforcement design must integrate a court-supervised collective compensation fund, specific execution of injunctive relief such as mandatory recalls, the application of disgorgement of profits and coercive fines (astreinte), and robust post-judgment monitoring. This study concludes that a comprehensively redesigned class action mechanism, synchronized with consumer protection law and coordinated with public enforcement, can simultaneously achieve restorative justice for victims and optimal deterrence for violators. This reconstruction enriches civil procedure theory and offers practical guidance for judges, legislators, and consumer advocates in combating the circulation of hazardous counterfeit goods.